Reproductive health as a gendered indicator of well-being: the case of ‘infertility’ - Remoaldo, Paula Cristina Almeida (2006)
Reproduction of human beings is also the reproduction of social relationships that constitutes a multidimensional process, in which biological but also emotional, cultural, economic aspects play a determinant role on the construction of the life cycle of the individuals. Therefore, the capacity of reproduction may be an essential ingredient of the experience and sense of well-being, mediated by gendered inequalities and sexual differences. During the last decades, deep cultural, economical and political transformations have intensified the changing of the demographic scenarios. The generalization of the access to modern contraception has created a diverse range of possibilities of ‘management’ of the reproductive careers. Along with the growing delay of the decision of having the first child, especially from the part of the women that are integrated on the market of paid work, having at least one child became a central point of the life of the modern families. But what happens when couples face infertility? Modern medicine is making impressive advances on what refers to assisted conception techniques, which in several countries have been the subject of intense public discussion and debate. Social sciences – and particularly the feminist studies – have been contributing to the debate by analysing the socio-cultural dilemmas that are being raised in the context of new reproductive techniques, in addition to difficult ethical, personal, moral and political questions. But very few studies are examining the phenomenon of infertility, maybe due to several obstacles that are created when researchers try to identify and contact the individuals and couples that are experiencing the infertile condition. Drawing on the making of qualitative interviews to couples who were unable to carry on the project of having a biological child (focusing on the woman’s experiences and feelings) and who have undergone assisted conception procedures, this paper examines the concept of «reproductive health», perceived as something which evokes gender differences and that may be understood as an essential indicator of the perceptions and evaluations of well being and of ‘living life’ from the part of the individuals and of the families.